2016
DOI: 10.1007/s00264-016-3209-0
|View full text |Cite
|
Sign up to set email alerts
|

Negative impact of waiting time for primary total knee arthroplasty on satisfaction and patient-reported outcome

Abstract: Waiting time longer than six months negatively influenced post-operative satisfaction and patient-related outcome at one year after TKA. These findings may have important clinical implications regarding the prioritization of patients on wait lists or for optimization of treatment while patients wait for surgery related to the management of the mental health and anxiety in order to reduce post-operative dissatisfaction and improve patient-reported outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 27 publications
1
27
0
2
Order By: Relevance
“…In fact, apart from the degree of disability, retirement status and socioeconomic status were found to influence the scores of LSR [27,31]. A recent study showed that waiting time longer than 6 months negatively influenced post-operative satisfaction and patientrelated outcome because of a lower level of functional reserves and mental health [32]. In such cases, we believe that LSR could also reflect the negative influence brought by the long waiting period, which has been reported to cause a significant deterioration in quality of life and high psychological distress [33].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, apart from the degree of disability, retirement status and socioeconomic status were found to influence the scores of LSR [27,31]. A recent study showed that waiting time longer than 6 months negatively influenced post-operative satisfaction and patientrelated outcome because of a lower level of functional reserves and mental health [32]. In such cases, we believe that LSR could also reflect the negative influence brought by the long waiting period, which has been reported to cause a significant deterioration in quality of life and high psychological distress [33].…”
Section: Discussionmentioning
confidence: 99%
“…[11] Patients waiting more than 6 months for surgery have been shown to experience increased anxiety, depression and unhappiness. [12] Characteristics of an efficient theatre service include prompt starts, quick changeovers, minimal intraoperative delays and few overrunning cases. [13] Efficiency must begin with appropriately booked elective operating lists.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Generally, neither pain nor function seemed to worsen for patients waiting less than 6 months for knee or hip replacements. [3] Our hospital waiting list had a wide range of waiting times, which ranged from 0 to 1 880 days.…”
Section: Discussionmentioning
confidence: 93%